Response to radioiodine in male hyperthyroid patients at Tygerberg Hospital - Onimode, Yetunde Ajoke (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Medical Imaging and Clinical Oncology. Nuclear Medicine))--University of Stellenbosch, 2009.